Perovskite nanostructures : leveraging quantum effects to challenge optoelectronic limits - Kulkarni, Sneha Avinash (2020)
Metal halide perovskites have affirmed their pedigree as extraordinary semiconducting materials, exhibiting properties rivalling those observed in single crystal compound semiconductors. Perovskites show tremendous versatilities in both structure and composition tuning, and therefore applications ranging from optoelectronics to X-ray imaging and spintronics, neuromorphic electronics are emerging. Moreover, when their dimensions become comparable to the exciton Bohr radius, perovskite nanostructures and layered systems display remarkable properties because of quantum confinement. Nanostructured and lower dimensional layered perovskites exhibit properties that are yet to be fully exploited such as extraordinarily high luminescence, narrow emissions, high exciton binding energies, strong non-linear phenomena, and carrier cascade characteristics. This review, while highlighting the frontier phenomena that continue to be unravelled, outlines how confined structures of these materials have demonstrated properties that promise to unlock exceptional quantum phenomena to challenge the optoelectronic limits.